Pengaruh Keadilan Distributif, Keadilan Prosedural, Dan Kepuasan Kerja Terhadap Komitmen Organisasi - Ikka Kurniasyari; Didik Subiyanto (Universitas Hamzanwadi, 2021)
The purpose of this study was to determine the effect of distributive justice on organizational commitment. Knowing the effect of procedural justice on organizational commitment. Knowing the effect of job satisfaction on organizational commitment. Knowing distributive justice, procedural justice and job satisfaction have a simultaneous effect on organizational commitment. The population of this study were all employees of Indigo Batik Yogyakarta totaling 40 employees. The research sample of Indigo Batik Yogyakarta employees is where the entire population is sampled, so the sampling technique is the census method. Sample data was collected by distributing questionnaires. The number of questionnaire data that was processed was 40 questionnaires. Data processing in this study using multiple linear regression analysis techniques, assisted by the SPSS version 23.0 program. The results of this study indicate that distributional justice has a positive and significant effect on job satisfaction. Procedural Justice has a positive and significant effect on job satisfaction. Distribution justice has a positive and significant effect on organizational commitment. Procedural justice has a positive and significant effect on organizational commitment. Job satisfaction has a positive and significant effect on organizational commitment. Job satisfaction is able to mediate the effect of Distribution Justice on Organizational Commitment. Job satisfaction is able to mediate the effect of Procedural Justice on Organizational Commitment.